Distributed Network Systems From Concepts to Implementations - Jia, Weijia; Zhou, Wanlei (Network Theory and Applications, 2005)
This textbook covers both theoretical and practical aspects of distributed computing. It describes the client-server model for developing distributed network systems, the communication paradigms used in a distributed network system, and the principles of reliability and security in the design of distributed network systems. Based on theoretical introductions, the book presents various implementation strategies and techniques for building distributed network systems, including examples in TCP/IP communications, the use of remote procedure call and remote method invocation techniques, and the development of web-based applications, distributed databases, and mobile computing systems. Audience The book is suitable for self-study or for use in classes. Most parts of the book have been used by the authors in their teaching of various topics including distributed systems, computer networks, and distributed database systems. The book can also serve as an invaluable guide for computing professionals in their work for the design and implementation of distributed network systems.